AMBULATORY APPROACHES TO MEASURING INTRAINDIVIDUAL COGNITIVE VARIABILITY IN EVERYDAY LIFE - Sliwinski, M. (Innov Aging, 2017)
Intraindividual cognitive variability can impede accurate measurement of cognitive status and obscure detection of cognitive decline indicative of normative aging or preclinical AD. This paper evaluates the advantages and challenges of using smartphones to measure cognitive function in real-time and in naturalistic settings to better measure intraindividual cognitive variability in order to 1) better model proximal influences on cognitive function in ecological valid settings; and 2) improve the reliability of assessing cognitive status. Data are presented that illustrates the feasibility of using this approach in middle aged and older adults, as well as older adults with mild cognitive impairment (MCI). We show that brief (<1 minute) cognitive assessments made by smartphones have comparable, and in some cases superior, reliability and validity compared to standard neuropsychological tests. We discuss how this technology can be integrated into ongoing aging studies and general principles for designing ambulatory cognitive tests.